2023
DOI: 10.1002/pssr.202200439
|View full text |Cite
|
Sign up to set email alerts
|

Effects of High‐Pressure H2 and D2 Post‐Metallization Annealing on the Electrical Properties of HfO2/Si0.7Ge0.3

Abstract: High‐pressure annealing (HPA) in both hydrogen (H2) and deuterium (D2) environments is attempted on HfO2/Si0.7Ge0.3 capacitors as a post‐metallization annealing (PMA) approach. As compared with conventional forming gas annealing (FGA), a dramatic reduction in the interface state density (Dit) is achieved after both H2‐ and D2‐HPA processes at the equivalent temperature (300 °C) and time (30 min) by effectively passivating the Ge‐induced dangling bonds at the interface region. Meanwhile, the stress‐induced leak… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…It is worth mentioning that many studies have reported the effect of forming gas annealing (FGA) on transistor mobility enhancement [38][39][40]. An annealing atmosphere with deuterium (D 2 ) instead of hydrogen (H 2 ) can increase the mobility of hafnium-based MOSFETs to near 400 cm 2 /(V•s) at room temperature [41,42], but there is still much room for improvement. Therefore, it is important to investigate the effect of post-deposition annealing (PDA) temperature on the cryogenic transport properties of thin-layer hafnium-based MOSFETs in order to further enhance the mobility.…”
Section: Introductionmentioning
confidence: 99%
“…It is worth mentioning that many studies have reported the effect of forming gas annealing (FGA) on transistor mobility enhancement [38][39][40]. An annealing atmosphere with deuterium (D 2 ) instead of hydrogen (H 2 ) can increase the mobility of hafnium-based MOSFETs to near 400 cm 2 /(V•s) at room temperature [41,42], but there is still much room for improvement. Therefore, it is important to investigate the effect of post-deposition annealing (PDA) temperature on the cryogenic transport properties of thin-layer hafnium-based MOSFETs in order to further enhance the mobility.…”
Section: Introductionmentioning
confidence: 99%